تشخيص مدى توافر القدرات الجوهرية في شركة الحكماء لإنتاج الأدوية والمستلزمات الطبية: دراسة لآراء العاملين في شركة الحكماء لإنتاج الأدوية والمستلزمات الطبية - الصواف، محفوظ حمدون Alsawwaf, Mahfouz Hamdoun; يونس، عبدالله جار الله (جامعة كركوك - كلية الإدارة والاقتصاد, 2016)
The current research Holds it the perceptions of theory and other applied contribute to expand the circle of thought and consideration to the idea of core competencies as part of the movement of knowledge woos towards lay the foundations to build appropriate mechanisms to focus on the unique competencies and value and then work on investment, and generally tries to find the answer to the question follows:. What's the availability dimensions of the core competencies in the Alhokma company for the production of medicines and medical supplies? The conclusions showed availability of land the cognitive and process to basic components of the core competencies arranged by their importance where occupied information technology the first rank in which ,while he was human capital ranked last. Depending on that made a number of recommendations including: In spite of the importance diagnosis of the core competencies and investing, but the most important is to work to sustain and care for these competencies. Hoping to provide a modest add contribution in making Alhokma Company more interested, investment and take care of the core competencies, and in a form that makes it a performance more of an edge and distinctive than it is now.
يحمل البحث الحالي في طياته تصورات نظرية وأخرى تطبيقية تسهم في توسيع دائرة التفكير والنظر تجاه فكرة القدرات الجوهرية وذلك في إطار الحراك المعرفي الساعي نحو وضع أسس بناء الآليات المناسبة للتركيز على القدرات الفريدة وذات القيمة ومن ثم العمل على استثمارها، وبشكل عام يحاول البحث الإجابة عن التساؤل الآتي: ما مدى توافر أبعاد القدرات الجوهرية في شركة الحكماء لإنتاج الأدوية والمستلزمات الطبية؟ وأظهرت الاستنتاجات توافر الأرضية المعرفية والعملية للمكونات الأساسية للقدرات الجوهرية مرتبة حسب أهميتها حيث احتلت تقانة المعلومات المرتبة الأولى فيها، فيما كان رأس المال البشري في المرتبة الأخيرة، واعتماداً على ذلك قدمت عدد من التوصيات أهمها: على الرغم من أهمية تشخيص القدرات الجوهرية واستثمارها إلا أن الأهم من ذلك هو العمل على أدامة ورعاية هذه القدرات. أملين تقديم إضافة متواضعة تسهم في جعل شركة الحكماء أكثر اهتماماً واستثماراً ورعاية لقدراتها الجوهرية، وبالشكل الذي يجعلها ذات أداء أكثر تفوقاً وتميزاً مما هي عليه الآن.
Keywords: المنظمات -- الموارد البشرية -- القدرات الجوهرية -- التعلم المنظمي -- شركة الحكماء لصناعة الادوية والمستلزمات الطبية -- العراق